2004
DOI: 10.1038/sj.gt.3302250
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive gene therapy using recombinant adeno-associated virus delivery of extracellular superoxide dismutase protects heart against ischemic reperfusion injury, improves ventricular function and prolongs survival

Abstract: In high-risk patients, the ideal cardiovascular gene therapy requires a strategy that provides long-term protection of myocardium against episodes of ischemic/reperfusion injury. We report the development of an efficient, long-lasting preemptive gene therapy strategy in a rat model of ischemicreperfusion (I/R) injury of heart. At 6 weeks prior to myocardial injury, the human extracellular superoxide dismutase (Ec-SOD) gene was delivered by direct intramyocardial injections, using a recombinant adeno-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…The strategy for intramyocardial gene transfer has been described previously (1,30,36). Briefly, the AAV vector constitutively expressing LacZ or HO-1 ( Fig.…”
Section: Aav-mediated Intramyocardial Gene Delivery Leads To Longtermmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy for intramyocardial gene transfer has been described previously (1,30,36). Briefly, the AAV vector constitutively expressing LacZ or HO-1 ( Fig.…”
Section: Aav-mediated Intramyocardial Gene Delivery Leads To Longtermmentioning
confidence: 99%
“…Our group (1,36) reported previously that predelivery of antioxidant genes such as heme oxygenase-1 (HO-1) or extracellular superoxide dismutase to the myocardium provides a preemptive strategy for myocardial protection in the event of MI. HO-1, in particular, may be well suited as a therapeutic agent for myocardial protection, because the catabolic byproducts of heme metabolism, carbon monoxide (CO) and bilirubin, have been reported to exert pleiotropic cytoprotective effects, including reduction of oxidative stress (4,44,52), inflammation (39,57), and apoptosis (2,14,28,36,40,54), which are the principal pathological stimuli leading to irreversible myocardial damage following ischemia and reperfusion (I/R) (7,13,54).…”
mentioning
confidence: 99%
“…Gene transfer of EC-SOD-1 by direct intra myocardial injection using an AAV vector resulted in high level cardio-protection in rats at 7 days following ischemia and reperfusion injury (Agrawal et al, 2004). Using the rat working heart model of transient global ischemia it has been shown that thioredoxin is substantially decreased, whereas preconditioning by non-lethal ischemia elicited up-regulation of Trx expression and induced tolerance against severe ischemic stress (Turoczi et al, 2003).…”
Section: Antioxidant Therapies and Oxidative Stress In Heart Diseasementioning
confidence: 99%
“…Other antioxidant enzymes that have shown potential for protection against ischemic damage include extracellular superoxide dismutase (EC-SOD-1), thioredoxin (Trx), and glutathione peroxidase (GSHPx) (Agrawal et al, 2004;Yoshida et al, 1996;Turoczi et al, 2003;Maulik et al, 1999). Gene transfer of EC-SOD-1 by direct intra myocardial injection using an AAV vector resulted in high level cardio-protection in rats at 7 days following ischemia and reperfusion injury (Agrawal et al, 2004).…”
Section: Antioxidant Therapies and Oxidative Stress In Heart Diseasementioning
confidence: 99%
“…33 Antioxidant gene therapy has also proven useful in mouse models. 34 Neurotrophin and antioxidant gene therapy hold promise in treating deafness. 4 The major drawback is the capsid-induced immune response, 35 typically causing the clearance of infected cells within 10 days.…”
Section: Adenoviralmentioning
confidence: 99%